Four Different Reasons of Subcutaneous Emphysema With or Without Pneumomediastinum and Pneumothorax After Facial Bone Surgery. Issue 6 (28th September 2022) - Choung, Han-Wool; Choi, Young-Jun; Kang, Hyun; Lee, Ui-Lyong
Abstract : Abstract: In the present study, the authors report rare case series with subcutaneous emphysema with or without pneumomediastinum and pneumothorax after orthognathic and facial bone contouring surgery, compare their clinical and radiologic findings, and suggest precautions. Four patients who showed subcutaneous emphysema on follow up chest X-ray and computed tomography after orthognathic and facial bone contouring surgery were included in the study. In all cases post-op subcutaneous emphysema were detected, however, the aspect and mechanisms of post-op air spread were all different. After the conservative management with administering the O2 by nasal cannula or endotracheal tube, the symptoms were relieved except 1 patient who needed chest tube insertion and further supra-sternal incision. In conclusion, subcutaneous emphysema with or without pneumomediastinum and pneumothorax after orthognathic and facial bone contouring surgery can be occurred by cervical fascia injury or alveolar ruptures. To preventing those complications, traumatic naso-tracheal intubation, excessive positive pressure ventilation, intermaxillary fixation immediate after the surgery, and increase of intra-alveolar pressure of the patients should be avoided.